Ethnomedicinal Plants of Rajasthan Desert used in Herbal and Folk Remedies (Indian Journal of Arid Horticulture, 2013)
The Rajasthan desert is very rich in medicinal plant wealth. The medicinal plants of this region have great potential  to be used in drug and pharmaceutical industries. These medicinal plants have been used by local people, tribal communities,  vendors, native doctors such as Ojhas, Bhagats, Bhopas and experts of Ayurvedic fields since long time in herbal and folk  remedies. Kalbelia, Nats, Bhils, Raika, Banjara, Gadolia-Lohar, Garasia, Kathodi, Dhanka, Saharia, Damor and Meena  communities of this region have a rich knowledge of plants based traditional medicines. Ten ethnomedicinal plants like Calotropis procera (Ait.) R. Br., Cleome gynandra Linn. Clerodendrum phlomidis Linn., Echinops echinatus Roxb., Leucas  aspera (Willd.) Spreng., Mimosa hamata Willd., Moringa oleifera Lamk., Peganum harmala Linn., Sida cordifolia Linn.,  Solanum surattense Burm. have been selected for this research work. The present investigation is aimed to create awareness  about the ethnomedicinal value of the plants and their uses to draw the attention of pharmacologists, phytochemists and  pharmaceuticals.
Keywords: Ethno medicinal plants; Rajasthan Desert; Herbal and Folk Remedies